1993
DOI: 10.1002/cber.19931260606
|View full text |Cite
|
Sign up to set email alerts
|

Methylenphosphanyl‐Komplexe von Chrom, Molybdän, Wolfram, Eisen und Nickel: Synthese und Reaktionen

Abstract: Methylenephosphanyl Comple:r.es of Chromium., Molybdenum, Tungsten, Iron and Nickel -Syntbesis and ReacUvity "The reacHon of the functionalized Pie double bond systems x -P", qR)SiMe l [R = SiMel and X = Cl (la), Cp· (5a) or R -Pb and X = Br (1 b), Cp· (S b)1 wilh alkali carbonylmetallates or earbonyl eomplexes of group 6, 8. and 10 metals leads to thc formation of the transition metal-substituted phosphaalkenes J{M}-P= C(R)SiMeJ 3a -j and 4a -i J, in which the P-C fragment aets as a one-eleetron donor. Depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…[31]. 1 [10] 2 [11] 3 [8] 4 [12] P R P R Cp*(Et 3 P)Ni P C SiMe 3 SiMe 3 H P C NMe 2 NMe 2 5 [14] 6 [15] 7 [17] …”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…[31]. 1 [10] 2 [11] 3 [8] 4 [12] P R P R Cp*(Et 3 P)Ni P C SiMe 3 SiMe 3 H P C NMe 2 NMe 2 5 [14] 6 [15] 7 [17] …”
Section: Synthesismentioning
confidence: 99%
“…Reactions with protic reagents can either lead to CÀH (normal) or PÀH (inverse) products depending upon the polarity of the bond [Eqs. (14), (15)]. [8,46] Classical reactions of olefins, such as catalytic hydrogenation [47] and epoxidation [48] can only be achieved after [49] whereas hydrozirconation [50] leads to the P À H products [Eqs.…”
Section: Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, there are two major contributions to the 31 P chemical shift, namely a diamagnetic contribution reflecting the electron density associated with the low-coordinate P atom and another contribution, which is determined by the HOMOϪLUMO gap of the molecule. Small HOMOϪLUMO gaps in P-metallophosphaalkenes such as the aforementioned nickel compound or the complex [Cp* (CO) 2 FePϭC(SiMe 3 ) 2 ] (δ ϭ 641.5) [37] give rise to significant low-field shifts. The large valence angle at phosphorus [126.2(6)°] in the iron complex indicates that the energy of the nonbonding orbital as the HOMO is raised by sp 2 -hy-bridization, whereas the energy of the LUMO, which is the π* orbital, remains roughly unaffected.…”
Section: Nmr Spectramentioning
confidence: 99%
“…[15] A series of η 2 -ligated nickel(0) species were prepared. [16] It has been shown that for an η 2 -bonded ligand, the PϪC bond is longer than it is in the comparable η 1 -complexes or the free ligand systems. [17,18] An η 1 ,η 2 -complex of a phosphaalkene with two coordinated transition metal atoms {[M] ϭ Fe(CO) 4 }, type D, was first recorded by Appel et al [19] (see also ref.…”
Section: Plexes Type B {[M]mentioning
confidence: 99%